Peran Guru Dalam Mengembangkan Kognitif Anak Usia 5-6 Tahun Di TK Cempaka Ciamis - Zahara Reyna Adhitya; Dadan Nugraha; Gilar Gandana (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study explores the role of teachers in enhancing cognitive development in 5-6-year-old children at TK Cempaka, Ciamis, focusing on challenges, solutions, and supportive learning environments. Using a descriptive qualitative case study approach, data were collected through observation, interviews, and documentation from January to April 2025. Subjects included teachers, 6-year-old children, parents, and the principal. Findings highlight challenges such as limited training, indistinct cognitive delay symptoms, inadequate assessment tools, high workload, and social stigma. Proposed solutions include teacher training, simple screening tools, multidisciplinary collaboration, inclusive education systems, workload management, educational technology, and stigma reduction. Teachers can foster supportive environments through differentiated teaching, inclusive classroom culture, gamification, parent-specialist collaboration, positive behavior management, adaptive curricula, and continuous training. The study recommends these strategies to optimize cognitive development per Permendikbud No. 137 of 2014, enhancing inclusive early childhood education